DETERMINASI MOTIVASI HIERARKI MASLOW DALAM MEMPENGARUHI KINERJA DOSEN - Endah Finatariani; Yenni Cahyani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Fulfilling the performance of the tri dharma is not easy, especially in the field of research and community service. Lecturers are not only required to be scientific, but also to contribute energy, time and costs. Therefore, there needs to be a fulfillment of work spirit, so that lecturers always have reasons/motives in achieving the performance of the tri dharma. In fact, this research is to see the possibility of strengthening the performance of lecturers during the implementation of the tri dharma through the five motivational factors initiated by Maslow. In testing the phenomenon, a quantitative method is used, in order to obtain statistical conclusions in the form of estimated values. Furthermore, regression statistics were used as an analytical instrument. The research was conducted at Pamulang University with lecturers as the unit of analysis. The sampling technique uses simple randomness, where research questionnaires are distributed directly to respondents via google form. The results show that, Maslow's five motivational factors have a real/significant contribution to the achievement of performance. This explains that the fulfillment of various sources of work motivation can foster feelings of enthusiasm to achieve better performance. In fact, the most interesting thing from this finding is that lecturer motivation has unique characteristics, because the self-actualization motivation factor is the most dominant variable in the fulfillment of the tri dharma performance.